2022
DOI: 10.1186/s13014-022-01989-5
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy treatment modification for prostate cancer patients based on PSMA-PET/CT

Abstract: Background Prostate cancer is the most common cancer among men, and its diagnosis and treatment are improving. Our study evaluated how PSMA-PET/CT prior to treatment planning might improve the optimal management of prostate cancer radiotherapy. Methods This retrospective pilot study included 43 prostate cancer (PCa) patients referred to our radiation oncologist department, from the urology department, for radiation therapy. 18F-PSMA-PET/CT was orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…A retrospective study ( 29 ) demonstrated that radiotherapy plans had to be modified by an average of 60.5% due to PSMA-PET/CT findings. However, these data are to be treated with caution since the total number of patients enrolled in the trial was low (43), and the indications for irradiations were heterogeneous (curative, salvage, and metastasis treatment).…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study ( 29 ) demonstrated that radiotherapy plans had to be modified by an average of 60.5% due to PSMA-PET/CT findings. However, these data are to be treated with caution since the total number of patients enrolled in the trial was low (43), and the indications for irradiations were heterogeneous (curative, salvage, and metastasis treatment).…”
Section: Discussionmentioning
confidence: 99%
“…Before that, early detection of treatment is critical to controlling prostate cancer. 82 External beam radiation therapy (EBRT) is an effective curative treatment option for localized prostate cancer. A total of 10-20% of patients develop long-term toxicity after radiotherapy for prostate cancer.…”
Section: Prostate Cancermentioning
confidence: 99%
“…These changes entailed a change of surgical technique (7.4%), usually the addition of an ePLND, and change in radiotherapy dose (7.4%), mostly an increase in the amount and field of radiotherapy [ 42 ]. Karagiannis et al, (2022), also found that PSMA PET-CT modified radiotherapy treatment plans in approximately 60% of their patients, usually finding further locoregional or metastatic disease and thus implementing additional systemic therapy [ 50 ].…”
Section: Conventional Stagingmentioning
confidence: 99%